2010
DOI: 10.1021/ja105211w
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Carbon Dioxide Sorption in an Organic Molecular Porous Material

Abstract: The organic molecular porous material 1 obtained by recrystallization of cucurbit[6]uril (CB[6]) from HCl shows a high CO(2) sorption capacity at 298 K, 1 bar. Most interestingly, 1 showed the highest selectivity of CO(2) over CO among the known porous materials so far. The remarkable selectivity of CO(2) may be attributed to the exceptionally high enthalpy of adsorption (33.0 kJ/mol). X-ray crystal structure analysis of CO(2) adsorbed 1 revealed three independent CO(2) sorption sites: two in the 1D channels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
227
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(233 citation statements)
references
References 31 publications
4
227
0
2
Order By: Relevance
“…63 This value, however, is higher than the heat of adsorption values of À30 to À33 kJ mol À1 reported for adsorption of CO 2 in CB [6] micropores. 38 These results point to an adsorption mechanism wherein part of the CO 2 gas molecules are adsorbed physically in the CB [6] pores and the remaining CO 2 molecules are attached to the amine end of EA molecules in the modified material as mentioned before. The reduction in the amount of N 2 adsorbed in the sample should be due to the fact that EA selectively occupied most of the available sites in the surface cavities, edges and pore-mouths of the material where CO 2 molecules tend to adsorb less selectively compared to N 2 , thereby selectively reducing the amount of N 2 adsorbed in the modified material.…”
Section: View Article Onlinesupporting
confidence: 58%
See 1 more Smart Citation
“…63 This value, however, is higher than the heat of adsorption values of À30 to À33 kJ mol À1 reported for adsorption of CO 2 in CB [6] micropores. 38 These results point to an adsorption mechanism wherein part of the CO 2 gas molecules are adsorbed physically in the CB [6] pores and the remaining CO 2 molecules are attached to the amine end of EA molecules in the modified material as mentioned before. The reduction in the amount of N 2 adsorbed in the sample should be due to the fact that EA selectively occupied most of the available sites in the surface cavities, edges and pore-mouths of the material where CO 2 molecules tend to adsorb less selectively compared to N 2 , thereby selectively reducing the amount of N 2 adsorbed in the modified material.…”
Section: View Article Onlinesupporting
confidence: 58%
“…For example, Kim and co-workers recently reported that CB [6] recrystallized from HCl showed high selective adsorption capacity towards CO 2 over CO at 298 K and 1 bar pressure. 38 It can therefore be anticipated that the modification of CB [6], either by chemical or physical means, provides an alternate option for the enhancement of the adsorption ability. 39,40 The high quadrupolar moment of CO 2 can be efficiently used for sequestration by logically employing a polar functional group with a high affinity towards CO 2 for modifying the pores of CB [6].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Even though CB[8] is larger than CB [6], the size of the channels in 3 is almost the same as that of 1 or 2. Similar to 1 and 2, the channels of 3 were filled with water and formic acid molecules, which form a hydrogenbonded network (Figure 1 e).…”
mentioning
confidence: 99%
“…Following the same self-assembly approach, a smart use of supramolecular interactions, recently enabled the obtainment of metalfree purely organic frameworks. The intrinsic flexibility of the connections involved in the network formation allowed the realization of responsive materials with applications in fields like as gas adsorption [2], conductivity [3] and molecular transport [4]. Halogen bonding (XB) is a powerful tool in supramolecular chemistry [5], often seen in competition with the most commonly used hydrogen bond (HB).…”
mentioning
confidence: 99%
“…Here we show that it is possible to use XBs and HBs in a cooperative way for the construction of purely organic frameworks. [6] Two new ligands (meso and rac-4,4'- [1,2-bis (2,3,5,6-tetrafluoro4¬iodophenoxy)ethane-1,2-diyl]dipyridine) able to be involved in both XB and HB has been designed and synthesized. Using the selected ligands several purely organic open frameworks with different topologies were synthesized via XB and HB orthogonal self-assembly.…”
mentioning
confidence: 99%